1990
DOI: 10.1111/j.1432-1033.1990.tb15578.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐decorated micelle structure of sodium‐dodecyl‐sulfate–protein complexes as determined by neutron scattering

Abstract: The structure of the complex between sodium dodecyl sulfate (SDS) and a deuterated bifunctional enzyme, N-5'-phosphoribosylanthranilate isomerase/indole-3-glycerol-phosphate synthase (Mr 49 484), has been studied in dilute solution by small-angle neutron scattering. The complex nearly acquired its final size, as shown by molecularsieve chromatography, at the chosen SDS concentration of 1.6 mM, which is slightly below the critical micelle concentration of 1.8 mM (at the ionic strength of 0.1 M). The 452 amino-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 41 publications
3
113
1
Order By: Relevance
“…So about 72 SDS molecules (21 kDd288 Da) would bind to one urease subunit (72/840 = 0.086 SDS molecule/aminoacid residue). However, in the case of SDSPAGE the amount of bound SDS/g protein is known to be about 1.4 g. The recent report using neutron scattering shows that the bound SDS molecules/amino-acid residue are in the range 0.44-0.53 [24]. Comparing with those values it suggests that a relatively small amount of SDS binding was enough to induce the dissociation of urease into its subunits.…”
Section: Resultsmentioning
confidence: 69%
“…So about 72 SDS molecules (21 kDd288 Da) would bind to one urease subunit (72/840 = 0.086 SDS molecule/aminoacid residue). However, in the case of SDSPAGE the amount of bound SDS/g protein is known to be about 1.4 g. The recent report using neutron scattering shows that the bound SDS molecules/amino-acid residue are in the range 0.44-0.53 [24]. Comparing with those values it suggests that a relatively small amount of SDS binding was enough to induce the dissociation of urease into its subunits.…”
Section: Resultsmentioning
confidence: 69%
“…15 mM surfactant allows for only about one or two micelles per protein, which would clearly not be well-described by a fractal model. It has been suggested that for fractal structures the helical portions of the protein are contained within surfactant micelles [e.g., ref 17 in Ibel et al (2)], consistent with fact that the subdomains of BSA, which are composed of three R helices, contain one face that consists largely of hydrophobic amino acids (75). Thus, the kink-like conformations observed in Figure 6 may provide insight into the origin of the fractal structures obtained at higher surfactant concentrations, with the kinks providing seed points onto which micelles grow.…”
Section: Bsa Conformation Changes With Light (Sans)mentioning
confidence: 80%
“…When temperature scans were done in the presence of SDS, the protein remained soluble. The CD amplitude increased upon denaturation, when the native P-sheet secondary structure was lost and replaced by the helical secondary structure proteins assumed in association with SDS micelles (Mattice et al, 1976;Ibel et al, 1990). Thermal unfolding transitions so determined for TSPAN wild-type and two mutants are depicted in Figure 3C.…”
Section: Amino-terminally Shortened Folding Mutant Proteinsmentioning
confidence: 99%